ANALYSIS OF COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF WRINGINAGUNG VILLAGE, GAMBIRAN DISTRICT, BANYUWANGI REGENCY - Sadi; Puji Rahayu (MAN Insan Cendekia Jambi, 2021)
National development is a continuous process in an effort to improve people's welfare in a planned and directed manner in every field of life the people and the nation, the State of the Republic of Indonesia is able to realize the national goals as formulated in the 1945 Constitution. In village development activities there is also community participation. Participation is the involvement of a person or several people in an activity. Involvement can be in the form of mental and emotional as well as physical involvement in using all of its capabilities (initiative) in all activities carried out and supporting the achievement of goals and responsibilities for all involvements